The Role of Financial Inclusion and Digital Green Finance in Improving the Financial Performance of MSMEs in Bogor (Sustainable Development Insights, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting economic growth and employment in Indonesia. However, many MSMEs still face challenges related to limited access to financial services and the adoption of sustainable financial practices. This study aims to analyze the role of financial inclusion and digital green finance in improving the financial performance of MSMEs in Bogor. The research adopts a quantitative approach using survey data collected from 135 MSME owners. Data were obtained through structured questionnaires measured using a five-point Likert scale and analyzed using SPSS version 25. The results of the multiple linear regression analysis indicate that financial inclusion has a positive and significant effect on MSME financial performance. Furthermore, digital green finance also shows a positive and significant influence on MSME financial performance. Simultaneous testing confirms that both financial inclusion and digital green finance jointly contribute to improving MSME financial performance, with a coefficient of determination (R²) of 0.419, indicating that 41.9% of the variation in financial performance can be explained by these variables. These findings highlight the importance of strengthening financial accessibility and promoting sustainable digital financial systems to enhance MSME competitiveness and long-term business sustainability. The study provides important insights for policymakers, financial institutions, and MSME actors in developing strategies to support sustainable economic growth through inclusive and environmentally oriented financial systems.
Keywords: Financial Inclusion; Digital Green Finance; MSMEs; Financial Performance; Bogor